Do one-stage indications predict success following two-stage arthroplasty for chronic periprosthetic joint infection? - M. M. Kheir; C. G. Anderson; Y.-F. Chiu; A. V. Carli (Journal of Bone and Joint Infection, 2024)
Introduction: The 2018 International Consensus Meeting (ICM) proposed criteria for one-stage exchange arthroplasty in treating periprosthetic joint infection (PJI). Our study aimed to determine what proportion of PJI patients met the 2018 ICM criteria and how this affected infection-free survivorship for patients. Methods: All chronic PJI patients treated with two-stage exchange within our institution between 2017–2020 were retrospectively reviewed. Included cases met 2011 Musculoskeletal Infection Society (MSIS) criteria for PJI and had a 2-year minimum follow-up. Treatment success was defined as Tier 1A in the 2019 MSIS working group definition. ICM one-stage criteria included non-immunocompromised host, absence of sepsis, adequate soft tissue for closure, known preoperative pathogen, and susceptibility. Immunocompromised host was analyzed as two separate definitions. Kaplan–Meier survivorship, Cox regression, and univariate analyses were performed. Results: A total of 293 chronic PJI patients were included. Overall, treatment failure occurred in 64/293<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="39pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="87b2addae142e329623fa3359cfe0826"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="jbji-9-75-2024-ie00001.svg" width="39pt" height="14pt" src="jbji-9-75-2024-ie00001.png"/></svg:svg> (21.8 %) patients. Only 13 % (n=37) met ICM criteria definition no. 1 for one-stage exchange; 12 % (n=33) met definition no. 2. In both definitions, infection-free survivorship at 2 years did not differ between patients who met and did not meet criteria (p>0.05). Cox proportional hazard regression analyses demonstrated that the only variable predicting treatment failure was knee joint involvement (p=0.01). Conclusions: We found that a very limited number of chronic PJI patients were suitable for a one-stage exchange. Furthermore, the supposition that healthier hosts with known pathogens (the basis of the ICM criteria) yield better PJI treatment outcomes was not observed. These results justify the ongoing multicenter randomized control trial comparing one-stage versus two-stage treatment for chronic PJI.